Development and utilization of a novel hydrogen bonding enhanced collector in the separation of apatite from quartz. (April 2022) - Peng, Xiangyu; Liu, Wenbao; Zhao, Qiang; Liu, Wengang; Tong, Kelin; Zhao, Panxing
Highlights: Hydrogen bond functional group is introduced into amine collector molecules. A novel and high-efficiency collector HDMEA was synthesized in laboratory. Better selectivity was achieved by regulating the size of the polar group. The separation performance of HDMEA was superior to DDA. Abstract: In the light of the adsorption difference of cationic collectors on quartz and apatite, an additional hydrogen bond functional group can be introduced into the traditional collector molecule—dodecylammonium acetate (DDA) to achieve high-efficient separation of minerals. In this study, a new surfactant—N-(2-hydroxy-1, 1-dimethylethyl) dodecylamine (HDMEA) was synthesized in our laboratory and acted as a new-type amine collector in the reverse flotation separation of apatite from quartz. The results of micro-flotation tests indicated that the separation performance of HDMEA was significantly better than that of DDA. When the concentration of HDMEA was 20 mg/L at pH 6.43, the apatite with 38.57% grade and 95.8% recovery could be achieved in mixed-flotation tests. The adsorption mechanism of DDA and HDMEA on quartz and apatite was comparably explored by the measurements of zeta potential, FTIR, contact angle, and AFM as well as the DFT calculations. These results demonstrated that improving the hydrogen bonds adsorption on quartz (by –NH- and –OH groups) and increasing the steric-hindrance effect on apatite help to achieve efficient flotation separation of quartz and apatite.